2021
DOI: 10.1002/brb3.2284
|View full text |Cite
|
Sign up to set email alerts
|

Wake‐up strokes are linked to obstructive sleep apnea and worse early functional outcome

Abstract: Background and Aims: Presence of sleep-disordered breathing (SDB) and especially obstructive sleep apnea (OSA) is a known risk factor for ischemic stroke. Additionally, SDB effects negatively on recovery after stroke. Up to one fourth of strokes are present on awakening. The link between OSA and wake-up stroke (WUS) has been suggested.We aim to determine the association between OSA and WUS in a Finnish stroke unit cohort. Material and Methods: An observational prospective longitudinal study consisted of 95 TIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…A prior study with 95 TIA and mild to moderate stroke patients showed that WUS was associated with moderate-to-severe OSA and worse short-term outcomes. 14 We also found a strong correlation between WUS and SDB, with patients with WUS having an approximately 21.91 times higher risk of SDB when compared with those without WUS. A possible explanation for this might be the occurrence of severe hypoxia at night, which contributed to the WUS in patients with SDB.…”
Section: Discussionsupporting
confidence: 63%
“…A prior study with 95 TIA and mild to moderate stroke patients showed that WUS was associated with moderate-to-severe OSA and worse short-term outcomes. 14 We also found a strong correlation between WUS and SDB, with patients with WUS having an approximately 21.91 times higher risk of SDB when compared with those without WUS. A possible explanation for this might be the occurrence of severe hypoxia at night, which contributed to the WUS in patients with SDB.…”
Section: Discussionsupporting
confidence: 63%
“…Their meta-analysis included 13 studies and showed that SAS-prevalence is significantly higher in WUS patients [ 8 ], with a significantly higher severity of sleep apnea according to AHI and ODI ( p = 0.017 , and p = 0.035 ). This topic was researched by Barreto et al, Haula et al, and Schütz et al [ 32 , 33 , 34 ] and the results of cited studies suggested that preexisting sleep apnea is associated with the occurrence of WUS or even with worse short-term outcomes measured in mRS [ 33 ]. Kim et al in 2018, using the Berlin Questionnaire [ 10 ], found that preexisting witnessed or self-recognized sleep apnea was significantly more frequent in WUS when compared to the non-WUS population (28.3% vs. 16.6%, p = 0.036).…”
Section: Discussionmentioning
confidence: 99%
“…6 Furthermore, obstructive sleep apnea is an independent risk factor for stroke, and studies suggest a relationship between obstructive sleep apnea and the occurrence of ischemic stroke during sleep, with the first signs of stroke first noted upon awakening from sleep (wake-up stroke). 7,8 The main obstructive sleep apnea symptoms include snoring, sleep fragmentation, witnessed apneas, morning headaches, decreased concentration, memory loss, and excessive daytime sleepiness. Excessive daytime sleepiness is a common symptom in stroke individuals and can be explained by insufficient sleep, sleep fragmentation, or the presence of sleep disorders.…”
Section: Introductionmentioning
confidence: 99%